If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f = -2f + -9 Reorder the terms: f = -9 + -2f Solving f = -9 + -2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '2f' to each side of the equation. f + 2f = -9 + -2f + 2f Combine like terms: f + 2f = 3f 3f = -9 + -2f + 2f Combine like terms: -2f + 2f = 0 3f = -9 + 0 3f = -9 Divide each side by '3'. f = -3 Simplifying f = -3
| -84-8x=9x+18 | | 156-7x=29x+24 | | 145-6x=3x+10 | | 8f=-2f-10 | | 9x=125 | | 2a+12=6 | | 7x=-64 | | 7x+32=-32 | | x=5000 | | a+6=4 | | x=2100 | | 12+56= | | 6=9x | | 0=9x-6 | | -16=8x | | 23=18+5x | | e=9-2e | | 4x=6x-11 | | 40=41+x | | 18y-6=-18 | | 18y-6=-10 | | 6p-5=7 | | 30=15x | | t=15x | | 6y^3-7y^2-7y+6=0 | | 20z-1+36=5z+5 | | 30-x=10+0.5x | | 11=21a | | 6m=x | | 4(-2z-5)-7=10 | | 35-6= | | 100*20= |